Gait analysis and body composition after treatment of quadriceps tendon ruptures showed equal results independent of suture anchor or transosseus repair technique used: a pilot study. Issue 26 (17th December 2020) - Hasenoehrl, Timothy; Palma, Stefano; Keilani, Mohammad; Reschl, Martin; Vekszler, Gyoergy; Ambrozy, Clemens; Plesser, Stefan; Hajdu, Stefan; Crevenna, Richard; Widhalm, Harald Kurt
Abstract: Purpose: Suture anchor repair is a fairly new surgical technique for quadriceps tendon ruptures. It is supposed to be superior to the standard transosseus sutures because of biomechanical superiority and – due to a less invasive surgery – earlier rehabilitation onset. This study focused on analyzing functionality of the quadriceps muscle during gait as well as body composition between a suture anchor and a transosseus suture repair group and is the first study that undertook systematic gait analyses in this patient population. Materials and methods: Seventeen patients who underwent either suture anchor (9 subjects) or transosseus suture repair surgery (8 subjects) at two different trauma surgery centers between 2010 and 2015 were included. Gait analysis was performed with a three dimensional motion capture system (Vicon) and body composition was assessed with bioelectrical impedance analysis (Nutribox). Parametrical statistical analyses were conducted using independent t -tests. Results: No statistically significant differences were found in any outcome parameter of gait analysis or body composition measurement. Conclusion: Suture anchor repair shows equal results to transosseus suture repair technique regarding gait quality and body composition. Implications for rehabilitation: In a long term follow-up suture anchor repair shows similar results to the transosseus suture technique regarding body composition and musculus quadriceps function in gait. Without the implementation of an appropriate rehabilitation protocol incorporating the earlier load-carrying capacity, early biomechanical advantages of suture anchor technique over transosseus sutures might vanish over time. The decision which surgery technique might be best for the individual patient, should not be based on the expectation that suture anchor repair alone without considering appropriate rehabilitation would lead to long term functional advantages over transosseus suture technique.